Identification of Neoantigens and Construction of Immune Subtypes in Prostate Adenocarcinoma - Gao, Yukui; Wang, Guixin; Chen, Yanzhuo; Zhang, Mingpeng; Gao, Wenlong; Shang, Zhiqun; Niu, Yuanjie (Frontiers in Genetics, 2022)
Background: Messenger ribonucleic acid (mRNA) vaccine has been considered as a potential therapeutic strategy and the next research hotspot, but their efficacy against prostate adenocarcinoma (PRAD) remains undefined. This study aimed to find potential antigens of PRAD for mRNA vaccine development and identify suitable patients for vaccination through immunophenotyping. Methods: Gene expression profiles and clinical information were obtained from TCGA and ICGC. GEPIA2 was used to calculate the prognostic index of the selected antigens. The genetic alterations were compared on cBioPortal and the correlation between potential antigen and immune infiltrating cells was explored by TIMER. ConsensusClusterPlus was used to construct a consistency matrix, and identify the immune subtypes. Graph learning-based dimensional reduction was performed to depict immune landscape. Boruta algorithm and LASSO logistic analysis were used to screen marker gene-set of PRAD patients who may benefit from mRNA vaccine. Results: Seven potential tumor antigens selected were signiﬁcantly positively associated with poor prognosis and the antigen-presenting immune cells (APCs) in PRAD, including ADA, UPP1, NFKBIZ, SLC16A3, HDC, FYN, and RASSF4. Five immune subtypes of PRAD were identified by differential molecular, cellular, and clinical characteristics in both cohorts. C3&C5 had immune “hot” and immunosuppressive phenotype, On the contrary, C1&C2 had immune “cold” phenotype. Finally, the immune landscape characterization showed the immune heterogeneity among patients with PRAD. Conclusions: ADA, UPP1, NFKBIZ, SLC16A3, HDC, FYN, and RASSF4 are potential antigens for mRNA vaccine development against PRAD, and patients in type C1&C2 are suitable for vaccination.